Integrating Green Sukuk and Cash Waqf Linked Sukuk, the Blended Islamic Finance of Fiscal Instrument in Indonesia: A Proposed Model for Fighting Climate Change - Khairunnisa Musari (UIN Sunan Gunung Djati Bandung, 2022)
Indonesia is the world’s first global and retail sovereign Green Sukuk issuer. In four years since its first issuance in 2018, Green Sukuk has been issued seven times to finance or refinance the projects or programs of Eligible Green Sectors. Then, in order to support the development of social investment and productive waqf, the Government of Indonesia (GoI) also issues Cash Waqf Linked Sukuk (CWLS) by blending Islamic finance and impact investing for the Sustainable Development Goals (SDGs). CWLS is the first blended Islamic finance for the fiscal instrument in Indonesia, which integrates Islamic commercial finance and Islamic social finance. In order to tackle climate change, this study promotes the integration between Green Sukuk and CWLS as well as adopting the Eshamconcept toward Perpetual Green CWLS as a new green financing alternative. This collaboration can be an innovative one in the future as a fiscal funding source to fight climate change which today becomes the development agenda priority in line with the intensified intention of extraordinary weather. Climate change has brought a high-cost impact on vulnerable and low-income people. Along with efforts to achieve the SDGs and Paris Agreement targets, a financing gap holds up the route to tackling climate change. Therefore, by using a literature study on the best practice of Green Sukuk and CWLS in publications mainly sourced from the Ministry of Finance (MoF) Republic of Indonesia, this conceptual paper focuses on three issues, namely: (1) describing Indonesia's sovereign Green Sukuk; (2) describing the CWLS; (3) explaining a proposed Perpetual Green CWLS as an Islamic green financing alternative.